Gender Influence on Clinical and Electrophysiological Manifestations of Guillain-Barre Syndrome (GBS), and Response to Treatment (Medical Forum Monthly, 2024)
Objective: To study the gender influence on clinical and electrophysiological manifestations and response to treatment.Study Design: Retrospective / cross sectional studyPlace and Duration of Study: This study was conducted at the Neurology Department of Mayo Hospital Lahore for a period of seven months from October 2017 till April 2018.Materials and Methods: Patients fulfilling the Asbury and CornBlath’s Criteria for diagnosis of GBS were included in the study. Subtypes or variants of GBS were identified according to our defined operational definitions. All patients who showed progression of disease were treated with five sessions of plasmapharesis performed over 10 days. Clinical features, muscle power strength on admission and NCS/EMG and CSF findings and duration of hospital stay required for one grade improvement in MRC scale before discharge results were recorded on a specified proforma designed for this study. The results were analyzed using IBM SPSS version.Results: Twenty nine (29) patients fulfilling the Asbury and CornBlath’s Criteria for diagnosis of GBS were included in the study. There were 19 males and 10 females with M: F of 1.9:1. The mean age for male group (n=19) was 39(+16.92) with range 15 to 75 years. The mean age for female group (n=10) was 32.30(+8.05) with range 6 to 41 years. The mean muscle power in limbs on admission according to MRC grading in female group was 1.50 (+1.354) compared with mean muscle power in male group of 2.50 (+1.150). The various subtypes of GBS in male group were AMSAN 52.63% (10 out of 19 patients), AIDP 36.84% (7out of 19 patients) and AMAN 5.2% (one patient). In comparison AIDP was most common 70% (7 out of 10 patients) variant of GBS in the female group followed by AMSAN 30% and AMAN 10%. The respiratory distress requiring ventilator support occurred in 15% (3 out of 19) of male patients compared with none in female group. Bilateral facial weakness was seen in 26% (5 out of 19) male patients compared with 30% in female group. Dysphagia occurred in 21% (4 out 0f 19) in male group compared with 10% (1 put of 10) in female group. All patients with progression of disease after admission to hospital were treated with alternate day sessions of plasmapharesis for a total five sessions. For the male group mean duration of hospital stay for improvement in muscle power of limbs according to MRC grade of one from the baseline before discharge was 11.63(+ 12.584) days with range from 2-45 days. In comparison the mean duration of hospital stay for female group was 20.10 (+ 8.749) days with range from 3-30 days.Conclusion: In conclusion our study confirms significant gender influence on the clinical and electrophysiological manifestations of Guillain-Barre syndrome (GBS), and response to treatment. AMSAN was most common subtype in males and AIDP in females. Limb weakness was severe in female on admission and required prolonged hospital stay compared with males. Bilateral facial weakness, dysphagia and respiratory involvement were more common in males. This study has small sample size and larger studies are needed to confirm our findings.